CONDITIONS FOR THE OCCURRENCE OF DISCIPLINARY RESPONSIBILITY OF THE EMPLOYEE - Sitora SHOISLOMOVA (Scholar Express Journals, 2022)
This article is devoted to the conditions for the occurrence and bringing an employee to disciplinary responsibility. The concept of “misconduct”, its characteristic features, types of misconduct and their distinctive features are revealed. In addition, a detailed analysis of the elements of disciplinary misconduct and the basis for bringing an employee to disciplinary responsibility is given. This article also reflects the list of categories of employees whose concept of disciplinary misconduct is interpreted due to the special nature of the duties performed, such as judges, lawyers, employees of the Department for Combating Economic Crimes at the Prosecutor General's Office of the Republic of Uzbekistan, the Bureau of Enforcement at the Prosecutor General's Office of the Republic of Uzbekistan, etc. and provides a clear example from judicial practice on the issue, arising from labor relations in the field of labor discipline.
Keywords: Misconduct; disciplinary misconduct; elements of disciplinary misconduct,; factual basis